Participation in public administration revisited : delimiting, categorizing and evaluating administrative participation - Đurman, Petra (Array, 2020)
Participation has been a relevant issue in public administration research and theory for several decades, especially in old democracies. However, recent processes of globalization, Europeanization and digitalisation, coupled with diminishing citizens’ trust in public institutions, have again made the concept of public participation topical. The aim of this paper is to provide a theoretical reflection on the concept and substance of participation in public administration and on research efforts. In order to do so, administrative participation is first defined and distinguished from other types of participation in modern democracies (political and civil participation). Participation in public administration encompasses the processes through which the public is directly involved in regulative and implementation functions of administrative organizations, as well as in the oversight of their functioning. The three main categories of participation in public administration are elaborated – regulative, implementing and oversight participation – together with some apparent forms (instruments) within each category. The main principles upon which administrative participation is based are also explained – transparency, openness, responsiveness and trust. The final part of the paper contains an overview of the existing research and evaluation of participation in public administration. The twofold value of participation – intrinsic and instrumental – is explained, its potential benefits and shortcomings are listed, and a distinction between the process and outcome dimension of participation is elaborated. Although the literature has become rather extensive and refined, one can conclude that unambiguous findings on the practical effects of participation are still deficient, especially with regard to its dependence on different contextual – especially organizational – variables.